Development and Usability Evaluation of an Android-Based Marker-Based Augmented Reality Application for Residential Property Promotion - Devi Afriyantari Puspa Putri; Endah Sudarmilah; Fatah Yasin Al Irsyadi; Zildan Alfatih Agustian; Alif Pandu Raharjo (International Journal of Computer and Information System (IJCIS), 2026)
The growing demand for interactive digital marketing has encouraged the adoption of Augmented Reality (AR) to overcome the limitations of conventional property promotion media. However, existing studies have primarily emphasized system implementation or marketing outcomes, with limited attention to evaluating application quality from the users' perspective. This study aims to develop an Android-based marker-based AR application for residential property promotion, verify its functionality through black-box testing, and evaluate its usability using a validated and reliable evaluation instrument. The application was developed following the Four-D (4D) development model and implemented using Unity and the Vuforia SDK to integrate printed property brochures with interactive three-dimensional visualization. Functional verification was conducted using black-box testing, while usability evaluation involved 51 respondents, comprising 45 public users and six property developers. The evaluation instrument was first validated and tested for reliability before descriptive statistical analysis was performed. The results showed that all application features operated according to the specified functional requirements. The questionnaire demonstrated acceptable validity and reliability, with a Cronbach's Alpha coefficient of 0.678. User evaluation indicated positive acceptance, achieving overall scores of 85.11% from public users and 85.33% from developers. These findings demonstrate that the proposed application provides an effective and user-friendly approach to residential property promotion by combining interactive three-dimensional visualization with conventional printed brochures. The proposed development and evaluation framework may serve as a reference for future AR-based promotional applications